Study of Heat Generation and Power Losses in MultiCrystalline Silicon Photovoltaic Solar Module (Journal of Engineering, 2025)
A photovoltaic modules convert only a fraction of incident solar energy into electricity, with the remainder dissipated as heat through various loss mechanisms. This study makes an attempt to quantify the recoverable thermal energy from multicrystalline silicon photovoltaic modules under varying irradiance conditions for arid climates. Experimental measurements were conducted over six months in Baghdad, Iraq. Data were filtered to maintain 25°C module temperature across four irradiance levels (250, 500, 750, 1000 W/m²). Results demonstrate thermal losses increasing from 10.33% to 19.02% with rising irradiance, while recoverable thermal energy fraction (ξu) ranges from 29.72% to 35.06%. Module efficiency decreased from 18.1% at 500 W/m² to 16.7% at 1000 W/m², reflecting thermal loss dominance over optical gains. Spectral analysis revealed uniform distribution of recoverable thermal energy across the solar spectrum rather than infrared concentration. The quantified thermal losses provide fundamental data for hybrid photovoltaic-thermal (PV/T) system development optimized for high-irradiance arid conditions, supporting renewable energy advancement where abundant solar resources enable combined electrical and thermal harvesting.